Using the Military Instrument in Conflict Resolution: A Changing Paradigm - Oliveira, António (2014)
The characteristics of current armed conflicts have grown in complexity, and the operations carried out to solve them are often performed without the agreement of all of those involved. Accordingly, the traditional use of military forces in the resolution of conflicts seems to be undergoing a rapid evolution. In face of this mounting complexity, peace operations began to be considered as broader “military operations” guided by principles that in the past were limited to the execution of combat operations, materialized by the implementation and application of a complex set of techniques and activities. In this new paradigm, the same “peace” operation may comprise a wide range of activities, ranging from conflict prevention to medium and high intensity fighting operations, and including also parallel humanitarian support activities. For this reason, and in accordance with the concept of employment and the functions to be carried out, the performance of the military forces in current peacekeeping operations is based on the simultaneous completion of a set of tasks that are required to attain the required final military goal. In the presence of the wide range of tasks that need to be performed, a military force should have the resources and be organized based on multiple capacities and characteristics. Areas that in the past used to support the actual force have now assumed increased relevance and are perceived as being crucial, given that the main role of military forces is that of creating and maintaining a safe and stable atmosphere that enables the remaining sectors participating in the process to act. In an integrated approach system to conflict, the aim is that military forces attain and ensure safety conditions, and guarantee the necessary support so that other agents can come up with the most appropriate solutions to address the causes of conflict.